Lenalidomide treatment for multiple myeloma: systematic review and meta-analysis of randomized controlled trials. - Bo Yang; Rui-li Yu; Xiao-hua Chi; Xue-chun Lu (PLoS ONE, 2013)
Background In recent years, a number of randomized controlled trials (RCTs) have reported on lenalidomide as a treatment for multiple myeloma (MM). Herein, we report results of a meta-analysis of RCTs examining the efficacy and safety of lenalidomide for MM. Patients and methods Databases were searched using the terms "lenalidomide or revlimid AND multiple myeloma."RCTs evaluating initial or maintenance therapeutic outcomes were included. Main outcome measures were response rates, progression-free survival (PFS), overall survival, and adverse events. Results Seven trials were included (N = 192-614 participants). Lenalidomide doses and treatment regimens differed between trials. Complete response (CR) and very good partial response (VGPR) risk ratios (RR) favored lenalidomide over placebo (CR = 2.54, 95% confidence interval [CI] = 1.29-5.02; VGPR = 2.82, 95% CI = 1.30-6.09). The PFS hazard ratio favored lenalidomide over placebo (0.37, 95% CI = 0.33-0.41). For adverse events, neutropenia, deep vein thrombosis (DVT), infection, and hematologic cancer RR favored placebo over lenalidomide (neutropenia: 4.74, 95% CI = 2.96-7.57; DVT: 2.52; 95% CI: 1.60-3.98; infection: 1.98; 95% CI: 1.50-2.62; hematologic cancer: 3.20; 95% CI: 1.28-7.98). Conclusions Lenalidomide is an effective treatment for MM; however, treatment-related adverse events must be considered and appropriate adjustments and/or prophylactic treatment should be initiated where possible.